Knowledge, attitude, and practice of artificial intelligence among doctors and medical students in Syria: A cross-sectional online survey - Swed, Sarya; Alibrahim, Hidar; Elkalagi, Nashaat Kamal Hamdy; Nasif, Mohamad Nour; Rais, Mohammed Amir; Nashwan, Abdulqadir J.; Aljabali, Ahmed; Elsayed, Mohamed; Sawaf, Bisher; Albuni, Mhd Kutaiba; Battikh, Elias; Elsharif, Leena Abdelwahab Mohamed; et al. (Frontiers in Artificial Intelligence, 2022)
Artificial intelligence has been prevalent recently as its use in the medical field is noticed to be increased. However, middle east countries like Syria are deficient in multiple AI implementation methods in the field of medicine. So, holding these AI implementation methods in the medical field is necessary, which may be incredibly beneficial for making diagnosis more accessible and help in the treatment. This paper intends to determine AI's knowledge, attitude, and practice among doctors and medical students in Syria. A questionnaire conducted an online cross-sectional study on the google form website consisting of demographic data, knowledge, and perception of AI. There were 1494 responses from both doctors and medical students. We included Syrian medical students and doctors who are currently residing in Syria. Of the 1494 participants, 255 (16.9%) are doctors, while the other 1252 (83.1%) are undergraduate medical students. About 1055 (70%) participants have previous knowledge about AI. However, only 357 (23.7%) participants know about its application in the medical field. Most have shown positive attitudes toward its necessity in the medical field; 689 (45.7%) individuals strongly agree, and 628 (41.7%) agree. The undergraduate students had 3.327 times more adequate knowledge of AI than students in the first year. In contrast, the undergraduate 6th-year students had 2.868 times the attitude toward AI higher than students in the first year. The residents and assistant professors had 2.371 and 4.422 times the practice of AI higher than students, respectively. Although most physicians and medical students do not sufficiently understand AI and its significance in the medical field, they have favorable views regarding using AI in the medical field. Syrian medical authorities and international organizations should suggest including artificial intelligence in the medical field, particularly when training residents and fellowship physicians.